2010
DOI: 10.1002/hed.21230
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of invasion and migration of salivary gland adenocarcinoma cells by 5′‐nitro‐indirubinoxime (5′‐NIO)

Abstract: Taken together, these results suggest that 5'-NIO, even at low concentrations, may effectively inhibit the invasion and migration of SGT cells by suppressing beta1 integrin-mediated signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The current study first evaluated the anti-migration/invasion effects of Indox on a spontaneous PDAC mouse model and the underlying mechanisms using the mice-derived cell lines. Previous reports demonstrated that indirubin derivatives inhibited the migration and invasion activities in other cancer and endothelial cells [26], [27], [28], [29], [30], [31], [32]. Indox blocked the invasion of the human myeloid cell line KBM-5 by the down-regulation of MMP-9 [26].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The current study first evaluated the anti-migration/invasion effects of Indox on a spontaneous PDAC mouse model and the underlying mechanisms using the mice-derived cell lines. Previous reports demonstrated that indirubin derivatives inhibited the migration and invasion activities in other cancer and endothelial cells [26], [27], [28], [29], [30], [31], [32]. Indox blocked the invasion of the human myeloid cell line KBM-5 by the down-regulation of MMP-9 [26].…”
Section: Discussionmentioning
confidence: 93%
“…Indox blocked the invasion of the human myeloid cell line KBM-5 by the down-regulation of MMP-9 [26]. In another study, 5-nitroindirubin 3′-oxime (5NO 2 Indox) inhibited the migration and invasion of salivary gland ductal adenocarcinoma by suppression of beta1 integrin and MMP-2 and -9 [27]. Furthermore, 6-bromoindirubin 3′-oxime (6BrIndox) also blocked the migration and invasion potential of colorectal and invasive urinary bladder carcinomas, accompanied with down-regulation of MMP-2 and -9 [28], [29].…”
Section: Discussionmentioning
confidence: 98%
“…MMP activity has been related with tumor cell proliferation and migration (26). Proliferation is an important factor in metastatic progression.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have identified numerous alternative modes for the cytotoxic and antiangiogenic actions displayed by indirubin and some of its derivatives. Other actions of the indirubins include suppression of the VEGFR-2-mediated JAK/STAT3 signalling pathway by indirubin (13) [85]; inhibition of alternative kinases such as Fms-like tyrosine kinase 3 by indirubin-3'-oxime (14a) and its 6-bromo analogue [86]; and inhibition of polo-like kinase 1 [87] as well as downregulation of Notch-1 and inhibition of Integrin β1/FAK/Akt signalling by 5-nitroindirubin-3'-oxime (14b) [86,[88][89][90].…”
Section: Indirubin Is the Active Component In The Traditional Chinesementioning
confidence: 99%